Advancing Islamic Education with Game-Based Learning: Principles, Effects, And Implementation Obstacles - Zulkefli, Murni; bin Jamil, Asyraf Isyraqi (Journal of Islamic Educational Research, 2024)
This study examines the incorporation of game-based learning (GBL) within Islamic educational contexts, focussing on the alignment of GBL with Islamic pedagogical principles and its effects on student engagement and learning results. A qualitative research design was utilised, encompassing document analysis and focus group talks. The document analysis examined literature and educational resources pertaining to both Game-Based Learning (GBL) and Islamic education, while focus group conversations with educators from Islamic schools offered insights into their experiences and perceptions of GBL. The results demonstrate that GBL is congruent with various Islamic educational principles, including self-reflection and feedback, individualised learning, incremental learning, and cooperative learning. Educators indicated that game-based learning substantially boosts student enthusiasm and enhances academic performance. Nonetheless, problems including resource limitations, curriculum alignment, and the necessity for professional development were recognised. Recommendations for successful integration encompass the creation of game-based learning materials specifically designed for the Islamic setting, offering training for educators, and tackling resource constraints. This study emphasises that the incorporation of Game-Based Learning (GBL) into Islamic education presents a viable method for improving educational experiences, contingent upon the resolution of implementation challenges and adherence to Islamic standards.